SOCIAL BENEFITS OF ECOTOURISM: THE MONARCH BUTTERFLY RESERVE IN MEXICO - Juan Carlos Monterrubio; Gregoria Rodríguez; M. Marivel Mendoza-Ontiveros (Enlightening Tourism: A Pathmaking Journal)
Ecotourism can contribute to both positive and negative socioeconomic impacts at the local level. However, ecotourism’s socioeconomic impacts have received limited scholarly attention in the context of developing countries. Based on qualitative interviews and observations, this paper looks at the socioeconomic benefits of ecotourism in a local community in the Monarch Butterfly Reserve in Mexico. It was found that ecotourism replaced most of the economic activities in the locality; the use of forest resources for individual consumption and local trade was largely replaced by ecotourism-related activities. Benefits included locals’ consciousness of natural resources and a more systematic organisation of economic activities. Acknowledging that qualitative methods somehow limit the generalisation of these findings, practical implications for the destination are suggested.